2009
DOI: 10.1136/tc.2008.025841
|View full text |Cite
|
Sign up to set email alerts
|

Predicting smokers’ non-compliance with smoking restrictions in public places

Abstract: Objective: The present study aimed to identify the predictors of non-compliance with smoking restrictions among Greek college student smokers. Differences in attitudes to smoking bans and tobacco control policies between current smokers and non-smokers were also examined.Methods: Data were collected from college students (N = 229, Mage = 21.27, SD = 3.15).Measures included tobacco dependence, attitudes to tobacco control policies, outcome expectancy and normative beliefs. Results:The majority of current smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 22 publications
3
54
1
3
Order By: Relevance
“…Contrary to the results presented in this work, in Chaaya's studies there were no significant differences observed in compliance with the smoking ban between women and men [27]. In a work by Lazarus et al, among 229 students in the northern Greece, majority reported non-compliance with the smoking ban by smoking in every place they wanted to and where it was forbidden [28]. The analysis carried out by Yong et al on the basis of International Tobacco Control Southeast Asia Survey results showed that the reported compliance with the smoking ban in Malaysia was very high, i.e., 95%, whereas in Thailand this percentage was significantly lower, 51% [28].…”
Section: Discussioncontrasting
confidence: 53%
“…Contrary to the results presented in this work, in Chaaya's studies there were no significant differences observed in compliance with the smoking ban between women and men [27]. In a work by Lazarus et al, among 229 students in the northern Greece, majority reported non-compliance with the smoking ban by smoking in every place they wanted to and where it was forbidden [28]. The analysis carried out by Yong et al on the basis of International Tobacco Control Southeast Asia Survey results showed that the reported compliance with the smoking ban in Malaysia was very high, i.e., 95%, whereas in Thailand this percentage was significantly lower, 51% [28].…”
Section: Discussioncontrasting
confidence: 53%
“…Evidence has shown that smoke-free policies at work reduce the overall burden of exposure to SHS, eliminate smoking cues, encourage smoking cessation among smoker employees [3][4][5], and result in higher financial returns and overall profit for the company and the public health system [6]. The implementation of smoke-free policies, however, is not always welcomed by smokers, who may resist change and violate smoking restrictions [7]. Even in this policies [10].…”
Section: Introductionmentioning
confidence: 99%
“…Even in this policies [10]. This is even more important in countries such as Greece, where tobacco control policies are poorly implemented, and many smokers report violation of existing smoke-free regulations [7,16]. The objective of the present study was to assess nonsmokers' assertiveness in SMEs and identify the psychosocial drivers of assertive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Only a few studies have examined support for smoke-free laws at bars and/or restaurants among young adults specifically, all of which have used a cross-sectional design. [11][12][13][14][15] It is particularly important to understand levels of support among the young adult population, not only because some studies have shown their support to be lower than older adults, but also because young adults are often employed in bars and restaurants 16 and tend to frequent bars. 17 Most previous studies have been limited to college students and only inquired about smoke-free laws on campus.…”
mentioning
confidence: 99%
“…17 Most previous studies have been limited to college students and only inquired about smoke-free laws on campus. [12][13][14][15] One study, which used data from the same project as the current study, included a community sample of young adults and found that overall support for smoke-free laws in restaurants was 66% and in bars was 40%. The study also found that, as with the adult population, factors associated with increased support included being a nonsmoker and living with a local smoke-free law.…”
mentioning
confidence: 99%